Answer:
5
Step-by-step explanation:
Answer:
Q.5 ab=cd
Q.6 ad=bc
Q.7 ce=ae
Q.8 eb=ed
Q.9 angle D=angle B (opposite angle of parallelogram are equal)
let other angle of parallelogram be x.
angle A+angle B +angle C + angle D= 360° (sum of quadrilateral is 360°)
x+130°+x+130°=360°
2x+260°=360°
2x=360°-260°
2x=100°
x=100/2
x=50°
Q.10 similarly, angle b= angle d
let other angle be x.
x+61°+ x+61°=360°
2x+122°=360°
2x=360°+122°
2x=238°
x=238°/2
x=119°
Q.11 in quadrilateral opposite angles are equal and opposite angle of parallelogram are equal.
Q.12 in quadrilateral opposite angle are equal and opposite angle of parallelogram are equal.
Q.13 in quadrilateral opposite sides are equal and opposite sides are parellel and this property is also present in parallelogram.
q.14 in quadrilateral diagonal bisected each other and diagonal of parallelogram also bisect each other.
The whole problem is in the picture. I Hope this helps
Step 1
<u>Find the value of TS</u>
we know that
if PQ is parallel to RS. then triangles TRS and TPQ are similar
so
![\frac{TR}{TP} =\frac{TS}{QT}](https://tex.z-dn.net/?f=%5Cfrac%7BTR%7D%7BTP%7D%20%3D%5Cfrac%7BTS%7D%7BQT%7D)
solve for TS
![TS =\frac{TR*QT}{TP}](https://tex.z-dn.net/?f=TS%20%3D%5Cfrac%7BTR%2AQT%7D%7BTP%7D)
we have
![RP=2\ cm\\TP=18\ cm\\QT=27\ cm](https://tex.z-dn.net/?f=RP%3D2%5C%20cm%5C%5CTP%3D18%5C%20cm%5C%5CQT%3D27%5C%20cm)
![TR=TP+RP\\TR=18+2=20\ cm](https://tex.z-dn.net/?f=TR%3DTP%2BRP%5C%5CTR%3D18%2B2%3D20%5C%20cm)
substitute
![TS =30\ cm](https://tex.z-dn.net/?f=TS%20%3D30%5C%20cm)
Step 2
<u>Find the value of SQ</u>
we know that
![SQ=TS-QT](https://tex.z-dn.net/?f=SQ%3DTS-QT)
we have
![TS =30\ cm](https://tex.z-dn.net/?f=TS%20%3D30%5C%20cm)
![QT=27\ cm](https://tex.z-dn.net/?f=QT%3D27%5C%20cm)
substitute
![SQ=30\ cm-27\ cm=3\ cm](https://tex.z-dn.net/?f=SQ%3D30%5C%20cm-27%5C%20cm%3D3%5C%20cm)
therefore
<u>the answer is</u>
the value of SQ is ![3\ cm](https://tex.z-dn.net/?f=3%5C%20cm)
Answer: n = -2
Step-by-step explanation:
3n +2(n + 2) = 9n + 12
(simplify 2(n + 2)) =
3n + 2n + 4 = 9n + 12
(subtract 9n from both sides)
3n + 2n - 9n + 4 = 12
-4n + 4 = 12
(subtract 4 from both sides)
-4n = 8
(divide -4 from both sides)
n = -2